Contribution à la caractérisation physique, mécanique, et à la valorisation du bois de pin maritime (Pinus Pinaster) en panneaux composites bois-polymère - LAZRAK Charaf (Faculté des Sciences de Rabat, 2020)
The present work concerns the dendrometric, physical and mechanical characterization of the wood of four maritime pine trees, its valorization in wood-polymer composite panels (WPC) and the application of some analysis methods (FTIR, DRX, contact angle and SEM) on these panels.
Contribution to the physical and mechanical characterization and valorization of maritime pine (Pinus Pinaster) wood in wood-polymer composite panels.
Keywords: Physique; Physique